Struktur Komunitas Makrobentos Polychaeta Di Ekosistem Mangrove Desa Bedono Kecamatan Sayung Kabupaten Demak - Pribadi, Rudhi; Djunaedi, Ali; Niâ€™amillah, Niâ€™amillah (977-2407769)
Mangrove forest is a tropical coastal communities is dominated by several species of trees or characteristic shrubs that has the ability to grow in salty waters. The study aim was to describe structure community of Polychaeta Macrobenthos in the village of Bedono, district of Sayung, Demak Regency (06055â€™44â€S - 110029â€™42â€E) and has been conducted between April 2010 to September 2010. The area, due to its position in the northern coast of Java, has influence by Java Sea especially its long-shore current which in past decades has been changing due to the Semarang Port development. Effort has been made by OISCA, a Japan environmentally concerned NGO, to rehabilitate the area by planting mangrove even though the result is just still uncertain yet. This research was aimed to know the stucture of polychaeta macrobenthos communities Bedono Village, District Sayung, Demak Regency. This research used descriptive eksplorative method and while for the intake of sampel polychaeta conducted quantitative just taken that is only pursuant to volume unit. In this research, the location was divided into 4 stations, each with three replication of sampling transects. Intake sample conducted at fairish plot 1m x 1m with the deepness 10 cm. The result found 6 famili polychaeta : Nereidae, Amphiromidae, Eunicidae, Capitellidae, Arenicolidae, dan Acoetydae. There tedency that vegetation of mangrove progressively make abundance polychaeta very much.